A Conceptual Replication of Targeted Professional Development to Increase Teachers' Behavior-Specific Praise. Issue 1 (2nd January 2023) - Grasley-Boy, Nicolette M.; Gage, Nicholas A.; Reichow, Brian; MacSuga-Gage, Ashley S.; Lane, Holly
Abstract: Multitiered support for professional development (MTS-PD) is a framework for applying a three-tiered support system to teacher classroom management professional development through targeted training and coaching. In this study, we conceptually replicated two prior MTS-PD studies. Following a school-wide training on behavior-specific praise (BSP), we conducted screening observations to identify teachers in need of additional support. Four teachers were identified and agreed to participate in a multiple-baseline design study focused on providing a targeted PD on BSP followed by emailed and texted visual performance feedback. We observed a functional relation between performance feedback and teachers' increased use of BSP among participants. Teacher acceptability surveys indicated the teachers approved of the performance feedback intervention and preferred receiving it via text due to ease of access. The results of this study provide further support for the MTS-PD framework along with meaningful considerations for future research. Impact Statement This study provides additional evidence of the effectiveness of using performance feedback to increase teachers' classroom management skills within a multitiered support for professional development (MTS-PD) framework. Following a screening for support need, we helped teachers increase their use of behavior-specific praise using emailed and texted visual performance feedback, an efficient and effective intervention that can be implemented by school-based practitioners.